Implementasi Metode Bernyanyi dalam Pengembangan Keterampilan Berbahasa Arab di TK Kemuning - Naely Kamilatul Azizah; Iin Herniati; Tri Miyani (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
Arabic is an international language that is closely related to Islam and is used in various countries in the world. Arabic is also referred to as the language of the Qur'an because the Qur'an is written in Arabic. According to the Big Indonesian Dictionary (KBBI) Arabic is defined as